Моделі банківського кредитування підприємств аграрної галузі - Трусова, Наталя Вікторівна; Трусова, Наталья Викторовна; Trusova, Natalia; Радченко, Наталія Геннадіївна; Радченко, Наталья Геннадиевна; Radchenko, Nataliia; Рубцова, Наталя Миколаївна; Рубцова, Наталья Николаевна; Rubtsova, Natalia (My University, 2021)
UK: Зростання ефективності діяльності аграрних підприємств позитивно вплинуло на стан кредитування галузі. В останні роки значно зросла пропозиція кредитних продуктів, з’являються нові форми банківського кредитування. У статті проведено аналіз сучасного стану кредитування аграрних підприємств; систематизовано кредитні пропозиції провідних банків України; визначені недоліки та переваги різних моделей банківського кредитування – класичний кредит на інвестиційні цілі та поточне фінансування, вексельні програми, партнерські програми. Проведено порівняльний аналіз умов, на яких банки готові фінансувати аграрний сектор – ліміт кредитування, строк кредитування процентна ставка, авансовий внесок, розмір комісій тощо. Для вибору ефективного кредитного продукту рекомендовано застосування методу аналізу ієрархій Т.Сааті; розроблено критерії першого та другого рівнів, що можуть бути використані під час прийняття рішення про вибір кредитного продукту. Визначені можливості фінтех- рішень на ринку аграрного кредитування. Обґрунтовано перспективи розвитку кредитних відносин з появою ринку землі. EN: The growth of the efficiency of agricultural enterprises had a positive effect on the state oflending to the industry. In recent years, the supply of credit products has grown significantly, new forms of bank lending are emerging. Today, the agricultural lending market has a large number of entities willing to finance the agricultural sector - banks, international financial institutions, credit unions, the state through support programs. The main creditors are banking institutions, which have recently increased attention to farmers, but still impose strict conditions - clean credit history, excellent financial reporting, impeccable reputation, successful operation of the enterprise for a sufficient period. The article analyzes the current state of lending to agricultural enterprises; systematized credit proposals of leading banks of Ukraine; identified shortcomings and advantages of different models of bank lending - classic credit for investment purposes and current financing, promissory note programs, affiliate programs. A comparative analysis of the conditions under which banks are ready to finance the agricultural sector - lending limit, loan term, interest rate, advance payment, the amount of commissions and more. It is established that the offers of banks are very similar in terms of the object of lending, repayment schedule, term and cost. In such conditions, it is very difficult to make the right choice of bank and credit product, the use of which will increase the efficiency of agricultural production. Along with a wide range of similar offers, the choice is complicated by the lack of knowledge about the specifics of bank lending. Therefore, in our opinion, it is important to constantly monitor the banking market and find favorable offers and lending models. To select an effective credit product, it is recommended to use the method of analysis of hierarchies T. Saati; developed criteria of the first and second levels that can be used when deciding on the choice of credit product. Possibilities of fintech-decisions in the market of agrarian crediting are defined. Prospects for the development of credit relations with the emergence of the land market are substantiated.
Models of bank lending to agricultural enterprises
Keywords: банк; аграрні підприємства; кредитні продукти; моделі банківського кредитування; партнерські програми; вексель; bank; agricultural enterprises; credit products; bank lending models; promissory note; affiliate programs